Determination of Systematic Thinking and Graduate Quality: Analysis of Human Resource Quality and Competence - Supriadi, Supriadi; Kemas Imron Rosyadi (Dinasti Publisher, 2022)
This research examines the identification of systems thinking and the quality of college graduates: analysis of skills and quality of human resources as a literature review of human resource management. The purpose of writing this article is to hypothesize the effect of variables to be used in research. The results of this library research are: The quality of human resources has an effect on systemic thinking; Competence has an effect on systemic thinking; The quality of human resources affects the quality of graduates; Competence affects the quality of graduates; and Systematic thinking affects the quality of graduates.